The association of environmental, meteorological, and pollen count variables with asthma-related emergency department visits and hospitalizations in the Bronx. (2nd September 2019) - Witonsky, Jonathan; Abraham, Ryan; Toh, Jennifer; Desai, Tulsi; Shum, Mili; Rosenstreich, David; Jariwala, Sunit P.
Abstract: Objective : To better understand how meteorological variables, air quality variables, and pollen counts collectively contribute to asthma-related emergency department visits (AREDV) and asthma-related hospitalizations (ARH) among pediatric and adult patients in the New York City borough of the Bronx. Methods : The numbers of daily adult and pediatric AREDV and ARH from 2001 to 2008 were obtained from three Bronx hospitals. After removing outliers, interpolating missing data, and standardizing variable values by scaling the data using z -scores, data were analyzed using Spearman rank tests and linear regression models for the full year and each season. Results : There were a total of 42, 065 AREDV and 1, 664 ARH at both Bronx hospitals. With the exception of a spring peak in AREDVs, AREDVs and ARHs follow a cyclical pattern, climbing in the fall, plateauing in the winter, dropping in the spring, and reaching a low in the summer. Among the 11 air quality, meteorological, and pollen count variables, temperature and tree pollen made the greatest contribution to AREDV with scaled coefficients of –0.337 and 0.311 respectively; equating to an additional AREDV for every 5.0-unit decrease in temperature and an additional AREDV for every 186.0-unit increase in tree pollen. These two variables were confirmed to have independent associations with AREDV prior to the data interpolation. Grass pollen was also found to have a relatively large contribution to AREDV during the summer with a scaled coefficient of 0.314, equating to an additional AREDV for every 2.3-unit increase in grass pollen. Conclusion : There are distinct peaks of increased AREDVs that are closely associated with increased tree pollen counts in the spring and decreasing temperatures in the fall. Early anticipation of these air quality, meteorological, and pollen factor changes based on ongoing surveillance could potentially guide clinical practice and minimize AREDVs in the Bronx.